Who lost the most? Financial literacy, cognitive abilities, and the financial crisis - Tabea Bucher-Koenen; Michael Ziegelmeyer (European Central Bank (ECB), 2011)
We study how and to what extent private households are affected by the recent financial crisis and how their financial decisions are influenced by this shock. Our analysis reveals that individuals with low levels of financial literacy are less likely to have invested in the stock market and thus are less likely to report losses in wealth. Yet, individuals with low financial literacy are more likely to sell their assets which lost in value (realize losses). This reaction to short-term losses has potential long-term consequences if individuals do not participate in markets' recovery and face lower returns in the long run.
Keywords: D91; D14; G11; 330; cognitive ability; financial crisis; financial literacy; life-cycle savings; Portfolio Choice; saving behavior